1999
DOI: 10.1038/sj.leu.2401319
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell engraftment and cell cycle phenotype

Abstract: Engraftment of hematopoietic stem cells in nonmyeloablated and minimally myeloablated hostsHematopoiesis is the most thoroughly characterized cell renewal, proliferation and differentiation system in biology. A central dogma is that the system is hierarchical with an orderly progression from stem cell to progenitor cell to differentiated end cell involving a progressive loss of proliferative potential linked to a gain of differentiated characteristics. A second dogma is that myeloablated treatment with radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Decreased migration may underlay the decreased engraftment seen for progenitors cultured ex vivo prior to transplantation. Similar results were seen by Dr. Quesenberry, who showed that changes in cell cycle phase of HSC induced by ex vivo exposure to cy-tokines may in part explain decreased engraftment seen in vivo [9]. He provided further suggestive evidence that changes in adhesion receptor expression (VLA4, VLA5, PECAM, L-selectin) and function (adhesion to stroma) correlate with decreased engraftment [10].…”
Section: Stem Cell Expansion and Homingsupporting
confidence: 69%
“…Decreased migration may underlay the decreased engraftment seen for progenitors cultured ex vivo prior to transplantation. Similar results were seen by Dr. Quesenberry, who showed that changes in cell cycle phase of HSC induced by ex vivo exposure to cy-tokines may in part explain decreased engraftment seen in vivo [9]. He provided further suggestive evidence that changes in adhesion receptor expression (VLA4, VLA5, PECAM, L-selectin) and function (adhesion to stroma) correlate with decreased engraftment [10].…”
Section: Stem Cell Expansion and Homingsupporting
confidence: 69%
“…[13][14][15] We sought to determine whether neutralization of TGF-␤, which we have demonstrated in the current studies to enhance cell-cycle progression at the molecular level, had an effect on human Immunocomplexes between cdk4 and cyclin D2 were detected only in the presence of anti-TGF-␤ antibody. After starvation in methionine-free DMEM for 4 hours, CD34 ϩ progenitors were metabolically labeled for 18 hours with 35 Smethionine/cysteine in the presence or absence of soluble TGF-␤1 or anti-TGF-␤ antibody.…”
Section: Effects Of Tgf-␤ Neutralization On Human Hematopoietic Stem mentioning
confidence: 99%
“…It has been proposed that cycling hematopoietic stem/progenitor cells do not engraft as well as quiescent cells in bone marrow (BM) transplantation settings. [13][14][15] Because TGF-␤ is a major factor in maintaining quiescence in murine and human hematopoietic stem cells, it was possible that TGF-␤ neutralization could have adverse effects in a transplantation setting. Our goal in the current study was to elucidate the molecular pathways by which TGF-␤ alters cell-cycle progression in CD34 ϩ cells as well as the impact of TGF-␤ neutralization on primary human hematopoietic stem/progenitor cell transplantation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of sufficient ALDH activity, higher levels of ROS and related compounds lead to increased HSC activation as well as a block in G 1 to S-phase transition in order to facilitate DNA check and repair of damage caused by the reactive compounds. This model would also explain the reduced number of transplantable HSCs noted in the CRU assays we conducted as HSCs that have moved out of G 0 have an engraftment defect [27]. If this model is validated in future studies, the ALDHs could join FOXO, AKT, and other important players in cell fate decision processes impacted by the oxidative stress and redox status of HSCs [28].…”
Section: Aldh Activity Impacts Multiple Cell Fate Processes In Early ...mentioning
confidence: 88%